Interaction of causative agents of sapronoses with the land plant Lithospermum erythrorhizon - N. F. Timchenko (Журнал микробиологии, эпидемиологии и иммунобиологии, 2022)
Background. A significant role in the ecology of the sapronotic pathogens Yersinia pseudotuberculosis and Listeria monocytogenes and in the epidemiology of the infections they cause is played by land plants used for food. These microorganisms are often found on plant substrates, they multiply on various vegetable and root crops. In this regard, it is relevant to study the viability and biological activity of Y. pseudotuberculosis and L. monocytogenes in contact with various land plants, including those that are not eaten, but are used in medicine.Aim. Study of the interaction of sapronotic pathogens Y. pseudotuberculosis and L. monocytogenes with callus cultures of the land plant Lithospermum erythrorhizon Siebold et Zucc.Materials and methods. The studies included strains of Y. pseudotuberculosis 512 serotype 1b, pYV+, 82MD+ and L. monocytogenes NCTC (4b) 10527 from the Collection of Somov Institute of Epidemiology and Microbiology, and cell culture from the roots of red-root gromwell Lithospermum erythrorhizon line VC-39 (from the Collection of FSC of the East Asia Terrestrial Biodiversity FEB RAS).Before the study, Y. pseudotuberculosis and L . monocytogenes were cultured 18–20 hours on nutrient agar pH 7.1–7.2. A working dilution of microorganisms was prepared (106 micobial cells per 1 ml) and applied at a dose of 100 μl to the surface of plant calli. Material samples were taken in dynamics after 3 and 14 days and prepared for scanning electron microscopy.Results. Y. pseudotuberculosis and L. monocytogenes formed biofilms on the surface of plant cells within 3 days after the start of the experiment. It was noted that Y. pseudotuberculosis destroyed the components of the plant cell membrane.Conclusion. New data obtained during the study expand the understanding of environments and forms of habitation, as well as the potential for pathogenicity of sapronotic pathogens in the environment.